Modeling economic growth in contemporary Czechia - Stavárek, Daniel; Tvrdon, Michal (Leeds : Emerald Publishing Limited, 2024)
Czechia has been a member state of the European Union for more than eighteen years. During this time, the Czech economy has undertaken a significant transformation. In the past decade alone, the Czech economy has had to cope with several external and internal shocks - the effects of the financial crisis and the subsequent crisis of the real economy, internal recession, and significant economic growth interrupted by the COVID-19 pandemic. Separated into four distinct parts, Modeling Economic Growth in Contemporary Czechia explores economic growth in Czechia from the perspectives of the dynamics of the economy, setting up of the economic policies, functioning of the markets and institutions, and the contribution of specific industry sectors to economic growth. Entrepreneurship and Global Economic Growth is Emerald's cutting edge Global Economic Growth book series, presenting modern examinations of economic growth at national, regional, and global levels. Each book in this series discusses different dimensions of the changing economic and industrial contexts and examines in detail their impact on the nature of growth and development.
Foreword / Jirí Rusnok -- Chapter 1. The Czech Economy in the Last Decade: Determinants and Obstacles to Economic Growth / Daniel Stavárek and Michal Tvrdon -- Chapter 2. Nominal and Real Convergence of Czechia with the Euro Area / Zuzana Szkorupová, Radmila Krkosková, and Irena Szarowská -- Chapter 3. International Trade and the Competitiveness of Czechia as the Fundamental Determinants of Economic Growth / Jan Nevima -- Chapter 4. The Role of Exchange Rate In Contemporary Czechia's Foreign Trade / Jana Simáková -- Chapter 5. Exchange Rate Commitment of the Czech National Bank / Jan Cernohorský, Libena Cernohorská, and Petr Teplý -- Chapter 6. Dilemma of the Czech National Bank: Factors of Adverse Macroeconomic Development in Czechia / Petr Rozmahel and Marek Litzman -- Chapter 7. Corporate Taxation in Czechia: A Proper Tax Mix Stimulating Economic Growth / Jana Janousková and Sárka Sobotovicová -- Chapter 8. Tax Policy to Internalize Road Transport Externalities / Petr David -- Chapter 9. Relationship Between General Government Expenditure and Economic Growth in Czechia / Irena Szarowská -- Chapter 10. Inflation Expectations in Czechia: Measurement and Determinants / Vojtech Konarík, Zuzana Kucerová, and Daniel Paksi -- Chapter 11. Regional Housing Prices in Czechia: Dynamics, Co-movements, and Drivers / Daniel Paksi and Ales Melecký -- Chapter 12. Efficiency of the Czech Labour Market: Do Institutions Matter? / Ales Franc -- Chapter 13. Polarisation of Employment in Czechia and Neighbouring Countries / Radek Náplava -- Chapter 14. Institutional Environment, Corruption and Their Impact on Economic Growth / Eva Kotlánová -- Chapter 15. Sectoral Indebtedness and its Influence on Output of the Czech Economy / Ladislava Issever Grochová and Michal Skára -- Chapter 16. The Contribution of Financial Institutions to Economic Growth / Iveta Palecková, Lenka Precková, and Roman Hlawiczka -- Chapter 17. The ICT Sector in Czechia and its Contributi
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Economic development -- Czech Republic; Business & Economics -- Development -- Economic Development; Economic growth; Development economics and emerging economies